Handwritten Digit Recognition Using Various Machine Learning Algorithms and Models (International Journal of Innovative Research in Computer Science & Technology, 2020)
Handwritten digit recognition is a technique  or technology for automatically recognizing and detecting  handwritten digital data through different Machine Learning  models. In this paper we use various Machine Learning  algorithms to enhance the productiveness of technique and  reduce the complexity using various models. Machine  Learning is an application of Artificial Intelligence that  learns from previous experience and improves automatically  through experience. We illustrate various Machine learning  algorithms such as Support Vector Machine, Convolutional  Neural Network, Quantum Computing, K-Nearest Neighbor  Algorithm, Deep Learning used in Recognition technique.
Keywords: Convolutional Neural Network; Support Vector Machine, HandWritten Digit Recognition; Artificial Intelligence; Deep Learning